Work-family conflict, work stress and coping strategies among selected call center agents - Emor, Jaeza G.
This is a descriptive study aimed to determine the work-family conflict, work stress and coping strategies of call center agents. Results showed that call center agents have a good balance relationship between work and family but high working stress.